Genetics : - Brooker, Robert J. (McGraw-Hill, 2009)
Genetics: Analysis and Principles is a one-semester, introductory genetics textbook that takes an experimental approach to understanding genetics. By weaving one or two experiments into the narrative of each chapter, students can simultaneously explore the scientific method and understand the genetic principles that have been learned from these experiments.